Menelisik Praktik Pengelolaan Dana Desa Melalui Sebuah Pemaknaan Kepala Desa - Sulaiha Wati; Faisol Faisol (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2023)
This research aims to determine the phenomenon of village fund management practices from planning, implementation of administration, and accountability through the meaning of awareness from the village head. The research uses a qualitative phenomenological approach to collecting data through observation, interviews, and documentation. The results of this research found that the Musrenbangdes in Mor Songai Village regarding the approval of village fund planning and budgeting only involved 3 BPD representatives. There is no transparency in the management of village funds in Mor Songai Village because the village fund management process is still in the learning stage. The implementation of administration in Mor Songai village did not run properly because administration was not carried out by the village treasurer. There is no accountability of the village head to the community due to weak BPD oversight of the village head's performance. The supervision and supervision carried out by the community in managing village funds did not work well because there was intimidation from the village head towards the community.